N-Heterocyclic Carbene Catalyzed Enantioselective Annulation of Benzothiazolyl Ethyl Acetates with 2-Bromoenals - Ni, Qijian; Xiong, Jiawen; Song, Xiaoxiao; Raabe, Gerhard; Enders, Dieter (Synlett, 2015)
An N-heterocyclic carbene catalyzed enantioselective [3+3] annulation of benzothiazolyl acetates with 2-bromoenals has been developed. The protocol provides a direct asymmetric synthesis of dihydro-1H-benzothiazolopyridinones in good to very good yields and medium ee values. In many cases, the virtually enantiopure heterocycles are available through a single recrystallization (99% ee).
Keywords: asymmetric synthesis; N-heterocyclic carbene; organocatalysis; annulation; dihydrobenzothiazolopyridinones